PENEGAKAN HUKUM TERHADAP TINDAK PIDANA EKSPLOITASI SEKSUAL ANAK DI WILAYAH HUKUM KOTA DUMAI - Tamara Aryani Siregar; Emilda Firdaus; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Children are the next generation of national ideals, have a strategic role in ensuring the existence of the nation and state and getting protection from parents, family, society, nation and state. But now there are still many problems found in children, one of which is sexual exploitation of children. This is very alarming where there is no strict treatment from the police, law enforcement in the field of sexual exploitation of children is still ineffective in view of the increasing cases of sexual exploitation of children, but they are reluctant to make reports due to public doubts about the police.This research is sociological research which is to see the influence of positive law on people's lives. This research was conducted in the jurisdiction of the Dumai City Resort Police, while the population and sample were all parties related to the problems examined in this study, data sources used, primary data, secondary data and tertiary data, data collection techniques in this study were carried out through observation, interview and literature review.From the results of the research conducted, it can be concluded, First, preventive and repressive law enforcement. Second, the obstacles faced are internal factors, internal factors such as the number of police personnel, the ability of personnel, the budget of the police institution, limited facilities and infrastructure. The external factor in the form of children is not realizing that he is a victim, fear of not obeying what was ordered by the perpetrators, public distrust of law enforcement, low awareness of the victims and lack of public awareness of the law and problems of sexual exploitation of children. Third, efforts to overcome barriers, namely fixing internal deficiencies, namely by adding personnel and increasing police capabilities by holding training and education on a regular basis, managing finances and adding facilities and infrastructure to existing needs, and fixing external deficiencies, namely providing understanding education towards children that what they do endangers them, restores children's trust through treatment by psychologists, instills a religious sense of fear of sin, restores the community's trust in the police and increases public awareness of the importance of law and the importance of child protectionKeywords: LawEnforcement – Crime - Sexual Exploitation of Children